Enhancement of Economic Independence and Introduction of Indonesian Culture for PIDs in the Philippines Through Indonesian Food - Iswari, Rani Dian; Musyaffa, Nadhif Fadhlan; Paksi, Arie Kusuma (International Journal of Public Devotion, 2023)
The life of the people of Indonesian descent (PIDs) in Glan, Philippines is still far from prosperous. Illegal citizenship status and poverty are the causes of the poor PIDs in Glan. Therefore, many of the PIDs in Glan end up working in the informal sector and earning below the standards of the local Filipino community. The International Community Service Team (KKNI) Glan from Universitas Muhammadiyah Yogyakarta was then empowered by holding a cooking class for traditional Indonesian snacks. The snacks that are taught are pisang gapit from East Kalimantan and dadar gulung from West Java. The main target of this program is PIDs who are members of the United Church of Christ of The Philippines (UCCTP) church in Glan. This program aims to reintroduce Indonesian culture through food and encourage the economic independence of PIDs in Glan. The methods used in this empowerment are program socialization, cooking training conducted with demonstrations, and mentoring carried out by inviting participants to practice directly. The material presented in this cooking class program can be a business opportunity for PIDs in Glan to improve their economy by utilizing local natural resources and also get to know Indonesian culture again. The result of this activity is that the PIDs in Glan have the opportunity to improve the Indonesian culinary business in the form of pisang gapit and dadar gulung, and the PIDs can preserve Indonesian culture even though they don't live in Indonesia.